Neonatal morbidity after cesarean section before labor at 34+0 to 38+6 weeks: a cohort study. (17th April 2016) - Prefumo, Federico; Ferrazzi, Enrico; Di Tommaso, Mariarosaria; Severi, Filiberto Maria; Locatelli, Anna; Chirico, Gaetano; Dani, Carlo; Lista, Gianluca; Orabona, Rossana; Zambolo, Chiara; Frusca, Tiziana
Abstract: Objective : To describe morbidity in neonates born by cesarean section (CS) before labor between 34 +0 and 38 +6 weeks, stratified by gestational age. Methods : Cohort study from five Italian tertiary care hospitals. Consecutive singleton pregnancies delivered by CS before labor between 34 +0 and 38 +6 weeks of gestation from January 2010 to August 2011 were included. Women in labor, with premature rupture of membranes, or with previous administration of steroids were excluded. The incidence of neonatal complication by gestational week was calculated. Results : A total of 1135 cases were analyzed. Composite adverse neonatal outcomes, respiratory distress syndrome, transient tachypnea and use of continuous airway positive pressure decreased from 50%, 28%, 5% and 22% at 34 weeks of gestation, to 4.7%, 1.0%, 0.9% and 0.3% at 38 weeks of gestation. Multivariate analysis showed that the only variable independently associated with composite adverse neonatal outcome was gestational age at delivery (adjusted odds ratio 0.49; 95% confidence interval 0.39–0.61). Conclusions : The prevalence of neonatal complications in newborns delivered by CS before labor halves at each week of gestation from 34 to 38 weeks. Nonetheless complications, and mainly respiratory problems, are still present at early term gestation.